Isolation and Identification of a Murine Norovirus Persistent Infection Strain in China - Na, Zhao; Bo, Jiang; Yifei, Yang; Fuyuan, Cao; Bin, He; Yanshu, Zhang; Huan, Jin; Jingliang, Su; Shuang, Li (Frontiers in Veterinary Science, 2020)
Murine Norovirus (MNV) is one of the most known viruses among viruses in mice. Because of the high prevalence of MNV in frequently used laboratory animals in biomedical researches, there is a significant impact of MNV. There may be different prevalence degrees and molecular characteristics of MNV in different regions around the world. Here, we reported an MNV strain “designated HBTS-1806” isolation from commercial mice’s feces that caused a detectable cytopathic effect (CPE) in RAW264.7 cells. According to electron microscopy, the virus was 50-70 nm in diameter. The complete genome of HBTS-1806 is 7383 nucleotides with a structure similar to that of MNV reference strains. According to phylogenetic analysis on the basis of the whole genome, HBTS-1806 shared nucleotide sequence identities of 90.2%-95.4% with other Chinese isolates reported. Analysis of amino acid sequence on the basis of ORF1 and ORF2 suggested that the isolated strain may be derived from recombination. Although no gross lesions or histopathological changes were found from mice infected with 5 × 105 TCLD50 of MNV by oral gavage inoculation, the intestinal virus loads lasted 12 weeks, suggesting a persistent infection strain of MNV isolate in China.